An Analysis of the Use of Electronic Money as a Transaction Instrument from the Perspective of Islamic Economics - Didiek Noeryono Basar (CV. Civiliza Publishing, 2025)
The rapid development of digital technology has driven a transformation in payment systems, moving from cash-based transactions to more efficient non-cash payment instruments, including electronic money. The emergence of electronic money addresses the growing public demand for practical, fast, and secure micro-transaction instruments, while raising questions about its compliance with Islamic economic principles. This study aims to analyze the use of electronic money as a transaction instrument from an Islamic economic perspective. The research employs a qualitative method with a literature review approach, utilizing secondary data obtained from academic journals, books, regulations, and fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). The findings indicate that electronic money is a payment instrument that stores monetary value electronically on a specific medium and is used for transactions with merchants affiliated with the issuer. From the perspective of Islamic economics, the use of electronic money is fundamentally permissible (mubah), provided that it complies with Sharia provisions and does not contain elements of maysir, gharar, riba, encourage israf (excessive consumption), or facilitate transactions involving prohibited objects. Therefore, electronic money can be accepted as a legitimate transaction instrument in Islamic economics, provided its implementation and management adhere to Sharia principles and applicable regulations.